Pola Asuh Orang Tua Dengan Kejadian Sibling Rivalry Pada Anakusia 1 – 5 Tahun - Siti Rofi’ah (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: The wrong developmental psychology in spite of pathogenic family patterns will impact sibling rivalry in bad condition. Many parents unknowingly put one of the children who loose in break up a fight between brothers.Objective: This aims of this research was to know parenting relationship with the Sibling Rivalry in Children 1-5 years old in Bejen Village, Bejen Distric of Temanggung Regency 2013.Method: Types of analytic study with cross sectional approach. This study population is mothers with children 1-5 years old. The sampling technique use total sampling, then analyzed by Chi-Square statistic test.The results of that result is obtained that there are 9 respondents of 32 respondents (28.1%) who applicate authoritative parenting, 6 (18.8%) of respondents who applicate authoritarian parenting, and 17 (53.1%) of respondents who applicate permissive parenting. There are 18 children (56.2%) experienced in sibling rivalry and 14 children (43.8%) have no experienced in sibling rivalry. Chi-square analysis with α (0.05), obtained ρ = 0.000.Conclusions: There is any parenting relationship with the incidence of sibling rivalry in children 1-5 years old. It states with the strong power correlation of 0.608.Key Words: Parenting, Sibling Rivalry